2007
DOI: 10.1002/ibd.20014
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of concurrent natalizumab treatment for patients with Crohnʼs disease not in remission while receiving infliximab

Abstract: The combination of natalizumab plus infliximab was well tolerated. Several positive trends suggested that treating patients not in remission with infliximab plus natalizumab had greater efficacy than treatment with infliximab alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(90 citation statements)
references
References 17 publications
0
82
0
8
Order By: Relevance
“…Interestingly, a drug called natalizumab, which has been used to treat autoimmune diseases such as multiple sclerosis and inflammatory bowel disease (50,51), is believed to function by blocking the ␣ 4 subunit of both CD49d (␣ 4 ␤ 1 ) and ␣ 4 ␤ 7 . Th17 cells have recently been shown to play a similar or increased role, compared with Th1 cells, in these two diseases (52).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a drug called natalizumab, which has been used to treat autoimmune diseases such as multiple sclerosis and inflammatory bowel disease (50,51), is believed to function by blocking the ␣ 4 subunit of both CD49d (␣ 4 ␤ 1 ) and ␣ 4 ␤ 7 . Th17 cells have recently been shown to play a similar or increased role, compared with Th1 cells, in these two diseases (52).…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events Natalizumab has demonstrated a consistent safety profile within controlled clinical trials of CD, with the most frequently reported (!10%) adverse events (AEs) including headache, fatigue, upper respiratory tract infections, and nausea [Elan Pharmaceuticals and Biogen Idec, 2010;Sands et al 2007;Targan et al 2007;Sandborn et al 2005;Ghosh et al 2003;Gordon et al 2001]. The most frequently reported AEs that resulted in discontinuation of natalizumab were exacerbation of CD (4.2%) and acute hypersensitivity reactions (1.5%).…”
Section: Safetymentioning
confidence: 99%
“…Natalizumab usado como monoterapia en dosis de 300 mg cada 4 semanas ha demostrado ser efectivo y seguro en EC refractaria a agentes anti-TNF [9][10][11][12][13][14][15][16][17] . Además, este fármaco ha demostrado ser eficaz en población pediátrica con EC con tasas de remisión clínica de 50% 18 .…”
Section: Discussionunclassified
“…Natalizumab es un anticuerpo monoclonal IgG4 anti-integrina-α4 humanizado que bloquea la adhesión y migración de leucocitos desde los vasos sanguíneos al tejido inflamado 7,8 . Este fármaco ha mostrado ser efectivo en inducir y mantener la remisión en pacientes con EC [9][10][11][12][13][14][15][16][17][18] . Sin embargo, su uso se ha visto limitado por reportes que han descrito el desarrollo de leucoencefalopatía multifocal progresiva (LMP), infección oportunista fatal causada por la reactivación del virus latente John Cunningham (JC), en pacientes con EC y esclerosis múltiple (EM) tratados con natalizumab 19,20 .…”
unclassified